2012
DOI: 10.1371/journal.pone.0029407
|View full text |Cite
|
Sign up to set email alerts
|

The Fitness Cost of Antibiotic Resistance in Streptococcus pneumoniae: Insight from the Field

Abstract: BackgroundLaboratory studies have suggested that antibiotic resistance may result in decreased fitness in the bacteria that harbor it. Observational studies have supported this, but due to ethical and practical considerations, it is rare to have experimental control over antibiotic prescription rates.Methods and FindingsWe analyze data from a 54-month longitudinal trial that monitored pneumococcal drug resistance during and after biannual mass distribution of azithromycin for the elimination of the blinding ey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 30 publications
4
35
0
Order By: Relevance
“…Other studies have reported similar changes in S. pneumoniae colonization and macrolide resistance following community-based mass administration of azithromycin for trachoma [17,27,28]. Seemingly, the fitness cost of macrolide resistance for S. pneumoniae ensures its replacement by susceptible strains when antibiotic selection pressure is removed [29].…”
Section: Post-intervention Carriage and Resistancementioning
confidence: 74%
“…Other studies have reported similar changes in S. pneumoniae colonization and macrolide resistance following community-based mass administration of azithromycin for trachoma [17,27,28]. Seemingly, the fitness cost of macrolide resistance for S. pneumoniae ensures its replacement by susceptible strains when antibiotic selection pressure is removed [29].…”
Section: Post-intervention Carriage and Resistancementioning
confidence: 74%
“…Apart from three case reports that demonstrated azithromycin MIC increases after treatment with azithromycin monotherapy (15,23,24) and studies that selected for macrolide resistance using erythromycin (25, 26), we are not aware of published data on mutational frequency with in vitro azithromycin exposure or on the stability of the mutants. Related to this, reduced azithromycin susceptibility may be acquired at a fitness cost that limits transmissibility, as appears to be the case with Streptococcus pneumoniae and Campylobacter jejuni (27)(28)(29). This may explain the sporadicity of the detection of isolates with reduced azithromycin susceptibility observed at individual geographic sites in the GISP.…”
Section: Resultsmentioning
confidence: 99%
“…However, many other chemicals, natural [e.g., plant-derived (Friedman, 2015)], and xenobiotic [e.g., solvents such as octanol, hexane and toluene (Ramos et al, 2002; Fernandes, 2003)], are also known to select for resistance genes. The prevalence of resistance genes in the environment are the result of a complex combination of factors, that reflect a dynamic balance of fitness costs and benefits: costs of carrying the ARG in the context of the host genome and environment (Maher et al, 2012; Roux et al, 2015); relative to the severity and frequency of hazard (Gullberg et al, 2011, 2014); relative to some physical environmental factors, such as temperature (Gifford et al, 2016) and microbial ecology (Amini et al, 2011), among others.…”
Section: Fundamental Questions Of Amr In the Environment: What Are Thmentioning
confidence: 99%